LIABILITY OF BOARD OF DIRECTORS IN FULFILLING THE RIGHTS OF EMPLOYEES (CASE STUDY ON PT. JOGJA TUGU TRANS) - , DIMAS ANDRI HIMAWAN, Dr. Sulistiowatio, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
According to agency theory, there is clear division between the ownership of the Company that is held by the shareholders and the management of the Company that is vested to the Directors. Therefore, the directors owe fiduciary duty to the Company (in this regard, the shareholderâs interest) and possess a very broad responsibility as the consequence of the authority given by the Law on Limited Liability Company. In fulfilling fiduciary duty, Board of Directors shall perform their duties by good faith, proper purpose, accountable independence and free from conflict of interest. However, in the practice, the Board of Directors of PT. Jogja Tugu Trans have acted not in accordance with law and regulation. It is shown by the improper application of work agreement and illegitimate dismissal of employees. Based on such facts, Author intents to analyze the liability of Board of Directors in relation with employment. In order to reach a conclusive finding, this undergraduate thesis shall be directed to attempt to answer the legal implication upon Board of Directors for the non-fulfillment of fiduciary duty and what has been done by General Meeting of Shareholder upon Board of Directors for the non-fulfillment of fiduciary duty. Author uses normative empirical research to find out such problem formulations. After conducting research, Author finds that the Board of Directors of PT. Jogja Tugu are not imposed any liability by the companyâs organ of PT. Jogja Tugu Trans. Moreover, the General Meeting of Shareholders of PT. Jogja Tugu Trans did nothing to respond the action of Board of Directors of PT. Jogja Tugu Trans which is not fulfilling the fiduciary duty as it is justified by the companyâs organ.